Morphometric analysis of soil aggregates in mined areas at different stages of recovery in the Amazon - Carvalho, Marcela Merides [UNESP]; Fengler, Felipe Hashimoto; Peche Filho, Afonso; Longo, Regina Marcia; Ribeiro, Admilson Irio [UNESP] (Universidade Federal de Santa Maria, 2022)
Mining has a strong influence on the Brazilian economy, however, extractive activity results in multiple damages to the ecosystem, as vegetation and the surface layer of the soil are removed, altering the natural pedological characteristics. Therefore, programs for the recovery of degraded areas become essential to mitigate or compensate for negative impacts on the environment. In this way, the understanding of soil quality indicators has been worked on to evaluate the process of recovery of degraded areas. Thus, the objective of this work was to develop and test a new approach to qualify the recovery of soil aggregation and reference ecosystems in the Brazilian Amazon (RO). For this, the geometric mean diameter (DMG) and the morphometric parameters: area, circularity, roundness and Feret diameter of the soil aggregates were determined. The parameters were evaluated in five different aggregate sizes, 6.0 mm, 4.0 mm, 2.0 mm, 1.0 mm and 0.71 µm, then multivariate analysis of variance (MANOVA) was performed, comparing the morphometric variables and aggregate sizes from each study area. The results obtained show a positive correlation between the values of area, circularity and Feret diameter of soil aggregates, indicating improvements in soil structure and vegetation. In this way, the proposed parameters demonstrated a high capacity to describe the soil quality and differentiate the recovery levels, presenting itself as an excellent indicator in the monitoring of degraded areas.
Análise da morfométrica de agregados do solo em áreas mineradas em diferentes estágios de recuperação na Amazônia
Keywords: Ecological Restoration; Environmental Indicators; Mining; Soil Quality